2009
DOI: 10.3109/08958370902767070
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes of the nasal mucosa induced by smoking

Abstract: Changes in the histopathology of the respiratory epithelium in response to cigarette smoking have been studied in depth in the lungs, but data on the nasal lining are lacking. The aim of the present retrospective study was to investigate the histological changes that occur in the nasal mucosa of smokers compared with non-smokers. The study group included 47 patients who underwent partial resection of the inferior turbinates. Archival nasal tissue samples were collected and examined by light microscopy: the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 29 publications
4
20
0
2
Order By: Relevance
“…It is widely accepted that cigarette smoking causes molecular injury throughout the airway epithelium with chronic inflammation as a common feature 2. In the nasal airway, smoking has been associated with inflammation, cellular hyperplasia, mucosal edema, and impaired ciliary function 3, 11, 12. Our study extends present knowledge by indicating a causal link between smoking and reduced nasal cavity dimensions and air flow, and impaired mucosal compliance.…”
Section: Discussionsupporting
confidence: 79%
“…It is widely accepted that cigarette smoking causes molecular injury throughout the airway epithelium with chronic inflammation as a common feature 2. In the nasal airway, smoking has been associated with inflammation, cellular hyperplasia, mucosal edema, and impaired ciliary function 3, 11, 12. Our study extends present knowledge by indicating a causal link between smoking and reduced nasal cavity dimensions and air flow, and impaired mucosal compliance.…”
Section: Discussionsupporting
confidence: 79%
“…Similar to the NECs studied here, it is likely that host defense responses in lower airway epithelial cells are modulated by epigenetic effects. The nasal epithelium resembles the airway epithelium morphologically, and smoking-related gene expression as well as histological changes, such as mucus production, are similar in nasal and airway epithelial cells (13,19,36). In airway diseases such as asthma, previous studies have demonstrated that DNA methylation changes in NECs from asthmatic children were associated with disease parameters in this population (1), suggesting that epigenetic modification in NECs can reflect changes in the lower airways.…”
Section: Discussionmentioning
confidence: 99%
“…Hadar et al explored histopathology changes in nasal mucosa of smokers and asserted that chronic toxic injury promotes metaplasia of epithelial cells, goblet cell hyperplasia, and edematous mucus secretion. Hadar et al further asserted that these changes are associated with cytokines interleukin (IL)‐4, IL‐13, and growth factors . Over time, it is conceivable that radiation therapy to the nasopharynx results in radiation‐induced impairment of epithelial proliferation and cell production, leading to hypoplasia and ultimate mucosal ulceration …”
Section: Discussionmentioning
confidence: 99%